Usability Evaluation of Learning Management System (LMS) Interface Universitas Pakuan Mobile Version With Heuristic Walkthrough Method - Dicky Abdurahman; Muhamad Saad Nurul Ishlah; Aries Maesya (Program Studi Ilmu Komputer, Universitas Pakuan, 2025)
This study aims to evaluate the usability of the mobile Learning Management System (LMS) interface at Universitas Pakuan using the Heuristic Walkthrough method. This method combines Heuristic Evaluation and Cognitive Walkthrough to systematically identify usability problems and assess their severity. Major usability issues were observed in navigation, search functionality, interface consistency, and user guidance, with an average severity rating of 2.72 for Heuristic Evaluation and 2.02 for Cognitive Walkthrough, indicating significant problems. A prototype was developed using the Goal-Directed Design approach, focusing on enhancing navigation, consistency, and functionality. Post-trial evaluation revealed a substantial reduction in severity rating to 0.17, highlighting only minor cosmetic issues. These findings underscore the effectiveness of the proposed approach in improving LMS usability. However, further research is recommended to refine responsive design and explore features beyond the current scope of evaluation.